Bilateral presence of two root canals in maxillary central incisors: A rare case study - M Kavitha; Kannan Gokul; B Ramaprabha; Amudha Lakshmi (Wolters Kluwer Medknow Publications, 2014)
Success in root canal treatment is achieved after thorough cleaning and shaping followed by complete obturation of the canal system. Therefore, endodontic therapy requires specific and complete knowledge of the internal and external dental anatomy, and its variations in presentation. The internal anatomy of the maxillary central incisor is well-known and usually presents one root canal system. This case report describes an endodontic treatment of traumatized both maxillary central incisors with two canal systems. Knowledge of dental anatomy is fundamental for proper endodontic practice. When root canal treatment is performed, the clinician should be aware that both external and internal anatomy may be abnormal.